p-Nitrotoluene Bromination Using Barium Fluorobromate Ba(BrF[4])[2]; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Sobolev V. I. Vasily Igorevich; Radchenko V. B. Vyacheslav Borisovich; Ostvald R. V. Roman Vyacheslavovich; Filimonov V. D. Viktor Dmitrievich; Zherin (Gerin) I. I. Ivan Ignatyevich (Chemical Technologies, 2014)
Title screen